Pengaruh Kepercayaan Dan Risiko Terhadap Sikap Dan Perilaku Dalam Memggunakan Aplikasi Mobile Berbasis Android - Agustinus Widyartono; Maria Josephine Tyra (Jurnal Ekonomi, 2016)
The aim of this research is to test the impact risk and trust variable toward behaviour with an attitude of android mobile application users as mediating variable. The total sample that was used in this research was 100 respondents. Based on the test, the instruments that used in this research are valid and reliable. This research used Component-Based SEM (Partial Least Square) as method analysis. The output from this research is: (1) Trust and attitude are mediating variables in relations between risk toward attitude and behaviour; (2) Risk as attitude form factor and people attitude to use android mobile applications; (3) Risk had negative relations with trust and attitude, as high risk perceived will reduce trust toward applications and attitude; (4) Trust had positive relations toward attitude and attitude had positive relations toward a behaviour is used android mobile applications.